IMPACT OF PERSONAL MOBILITY DEVICES ON THE RISK OF MAXILLOFACIAL INJURIES ACROSS DIFFERENT AGE GROUPS (American Journal of Interdisciplinary Research and Development, 2024)
Currently, there is a high demand for personal mobility devices, particularly "electric motor scooters." Today, this type of transport is widespread among modern countries, including Central Asian countries, and our country, Uzbekistan, is no exception. It has gained a place among other nations in making personal mobility devices available for public use.